FAKTOR PENENTU TERHADAP MINAT INVESTASI DI PASAR MODAL - Riana Tri Mukti; Idham Lakoni; Melvi Yansi (Yayasan Insani Mandiri Santani, 2026)
This study aims to determine whether financial literacy, financial efficacy, and technological development influence investment interest in the capital market among students in Bengkulu City. This study uses a quantitative explanatory research method to determine the influence of the independent and dependent variables. The sample size in this study was 150. The analysis used in this study is Smartpls Version 4 2026. The results of the path coefficient analysis show that Financial Literacy (X₁) positively and significantly influences students' investment interest in Bengkulu City (Y), with a path coefficient of 0.478, t-statistic 6.586 (>1.96), and p-value 0.000 (<0.05). Financial efficacy (X2) positively and significantly influences students' investment interest in Bengkulu City (Y), with a path coefficient of 0.119, t-statistic 5.872 (>1.96), and p-value 0.000 (<0.05). Technological development (X3) positively and significantly influences students' investment interest in Bengkulu City (Y), with a path coefficient of 0.323, t-statistic 5.626 (>1.96), and p-value 0.000 (<0.05). Simultaneously, the three independent variables (X₁, X₂, X₃) influence the investment interest of students in Bengkulu City (Y) with an R-squared value of 0.840 and an Adjusted R-squared value of 0.837. This means that 84.0% of the variation in investment interest is explained by this model, while 16.0% is influenced by external factors. The partial effect indicates a dominant order: Financial Literacy (47.8%) > Financial Efficacy (11.9%) > Technological Development (32.3%), with all p-values ​​0.000. Keywords: Financial Literacy, Financial Efficacy, Technological Development, and Investment Interest